Advances in Phenotyping Obesity and in Its Dietary and Pharmacological Treatment: A Narrative Review - Pujia, Roberta; Tarsitano, Maria Grazia; Arturi, Franco; De Lorenzo, Antonino; Lenzi, Andrea; Pujia, Arturo; Montalcini, Tiziana (Frontiers in Nutrition, 2022)
In recent times, it has become evident that there are individuals who, from a metabolic point of view, are affected by obesity but have a normal body mass index. There are also metabolically healthy individuals with a high body mass index who are thus are considered as to be affected by obesity obese. Understanding that individuals with obesity are phenotypically heterogeneous is a relatively novel concept which, although present in the scientific literature, unfortunately has not yet had an impact in clinical practice. However, common dietary approaches are not effective in treating large numbers of obese patients with obesity. This narrative review, based on the material searched via PubMed and the Web of Science up to October 2021, proposes a downsizing of the role of the body mass index in identifying the individual with “true obesity” truly obese”, since it is only partially useful, and suggests a new approach which also integrates the body composition and assessment of metabolic parameters. This approach leads to personalized therapies that work best for each obesity phenotype in reducing the risk of non-communicable diseases.